Implementation of the Scaffolding Method in Improving the Learning Outcomes of Islamic Religious Education on the Material of Signs of Baligh at SD Negeri 091609 Sinaksak - Harahap, Diana Fajar Anggraini; Apriani, Nurhapni; Saidah; Ritonga, Muhammad Ali Sukri; Marlina, Latifah; Hasanah, Siti (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
Learning about the signs of puberty plays an important role in equipping students with an understanding of the physical and psychological changes that occur during puberty. However, there are still obstacles in students' understanding due to the lack of the right approach in delivering the material. This study aims to apply the scaffolding method to improve students' learning outcomes in understanding the signs of puberty. The scaffolding method is applied through several stages, namely modeling (giving examples), bridging (bridging initial knowledge), contextualizing (connecting with everyday life), questioning (guiding with questions), scaffolding feedback (providing gradual feedback), independent practice (independent practice), and reflection & review (reflection and reinforcement). The application of this method allows students to gain a deeper understanding gradually, with assistance provided as needed until they can learn independently. The results of the study showed that the scaffolding approach was able to increase student involvement in the learning process, clarify the concepts taught, and significantly improve their learning outcomes. Thus, the scaffolding method can be an effective strategy in teaching the material on the signs of puberty and can be adapted in learning other materials.